Quality Enabling Conditions and Teaching-learning Process in Chemistry at Senior Secondary Level Teachers’ Perspective - Sharma, R K; Pareek, R B (JOURNAL OF INDIAN EDUCATION, 2022)
There are several factors which influence the regularity and performance of learners in the school and the learning environment of schools is one of them. Learning environment refers to the diverse physical locations, contexts, and cultures in which students learn. It gives the experience of pleasure or pain, success or failure, active involvement or passive listening, to the students. Proper learning of students depends on quality enabling conditions and teaching-learning process. Teachers play an important role in creating a learning environment, especially in the teaching-learning process. NCF 2005 (NCERT, 2005) recommends experiential learning in science and quality enabling conditions are required for it. In the present study, efforts have been made to study the quality enabling conditions and teaching-learning process of chemistry from the perspective of teachers in 20 senior secondary schools of Ajmer district of Rajasthan using mixed method (qualitative and quantitative) of research. It has been observed that schools under study lacks in desired quality enabling conditions and teaching-learning process and thus, interventions are needed to improve the quality.